Antartide. Il cuore bianco della Terra - Antarctica. The Earth's white Heart - BARONI, CARLO; a. cura di (Enrico Rainero, 1991)
Man was only to first set sight on the Antarctic at the beginning of the last century. Surrounded by a thick screen of fog and stormy seas, this distant and terribly hostile continent, completely uninhabited and totally different from any other known lands, was presented to the public of the time as an unknown and awful world, characterized by superhuman limits. The extraordinary nature of this wonderful continent immediately gave rise to great interest. Its exploration has involved many heroic protagonists from several countries, all of whom managed to express the best human and technological energies of their times. Its particular outlines, so unusual compared to the rest of the planet, are still more or less unaltered, in spite of the fact that today it is possible to reach the great ice sheet in a few hours by air and that satellite images can provide detailed documents of the most hidden corners of the continent. Scientific interest in the oceans, atmosphere, forms of life and the ice of the Antarctic has remained unchanged, if anything, it has increased even more. Alimentary and energetic resources of great importance are preserved in the ocean and on the continent. The Earth's white heart is composed of an enormous mass of ice, which represents a rich reserve of uncontaminated fresh water, regulates the variations in sea level and conditions the climate on a world scale. Moreover, the Antarctic ice sheets have registered all the moments in the evolution of the climate and environment, covering a long period in the history of the planet. In these last few years, research on the continent of ice has attracted a growing number ofscientists from the international community. Italy contributes to this undertaking with the National Programme of Antarctic Research (P.N.RA.) which, since 1985, has made it possible for many Italian researchers to carry out scientific investigation on the continent of ice. An enormous amount of work has been done. A great amount of energy and effort were involved in the research and ...